Adolescent Neural Responses to Antismoking Messages, Perceived Effectiveness, and Sharing Intention. Issue 2 (4th March 2019) - Kranzler, Elissa C.; Schmälzle, Ralf; O'Donnell, Matthew Brook; Pei, Rui; Falk, Emily B.
ABSTRACT: Health communication delivered via media channels can substantially influence adolescents' choices, and the effects of messages are amplified through interpersonal sharing. However, the underlying psychological and neurocognitive mechanisms that influence message effectiveness and likelihood of sharing are not well understood, especially among adolescents. Based on research in adults, we hypothesized and preregistered that message-induced neural activation in regions associated with self-reflection, social processing, and positive valuation would be related to greater perceived ad effectiveness and intentions to share messages. We focused on brain activity in meta-analytically defined regions associated with these three processes as 40 adolescent nonsmokers viewed advertisements from "The Real Cost" antismoking campaign. Perceived message effectiveness was positively associated with brain activity in the hypothesized social processing regions and marginally associated with brain activity in self-relevance regions, but not associated with brain activity in valuation regions. By contrast, intentions to share the messages were not associated with neural response in these 3 systems. In contrast to previous neuroimaging studies with adult subjects, our findings highlight the role of social cognition in adolescent processing of persuasive messages. We discuss the possibility that the mental processes responsive to effective and shareworthy messages may reflect developmental processes pertinent to media effects.